Diffusion tensor imaging in assessment of demyelinating diseases of central nervous system - Mukherjee, Arindam; Garga, Umesh Chandra (International Journal of Research in Medical Sciences, 2020)
Background: Conventional MR plays an important role in detection of demyelinating lesions. Involvement of the lesion core, perilesional region and normally appearing white matter (NAWM) cannot be quantified using routine T2/FLAIR sequences. DTI is an important tool in assessment of anisotropy in affected and apparently normal region of brain. 3D Tractography maps are useful in showing white matter fibre loss. Aim was the assessment of white matter damage and neuroaxonal loss using DTI in demyelinating lesions Methods: Cross sectional observational study including clinically suspected 30 patients of demyelinating disease. Patients were studied in 3Tesla Siemens Skyra MRI scanner with phased array coils. T1w, T2w, FLAIR, DWI, DTI, post contrast T1w images were included and FA, ADC, Tractography maps were generated. ANOVA test and BONFERONI analysis were used. Results: We found mean FA of core lesion was 0.307±0.06, of perilesional region 0.444±0.03 and NAWM 0.567±0.06. The mean ADC value of core of the lesion was 1.24×10-3mm2/sec±0.11×10-3mm2/sec, perilesional region 1.16×10-6mm2/sec ±0.1×10-3mm2/sec and NAWM 1.04×10-3mm2/sec±0.06×10-3mm2/sec. Conclusions: DTI is a useful MR technique that allows quantification of extent of demyelination in the white matter measuring FA and ADC values. The FA values which denote diffusivity and directionality are more reliable marker of demyelination compared to ADC values. DTI Tractography shows white matter tract disruption which may play role in assessing clinical outcome of patients.